Money matters: global banks, safe assets and monetary autonomy (2021)
This paper depicts an often neglected channel of transmission of monetary policy, namely international safety appetite, as an important source of production and risk-taking international monetary spillovers. The model features a local economy with exogenous financial frictions that lead firms to need both local and foreign financing to pay for their factors of production. Global and local risk-averse banks supply firms with risky loans while buying safe assets to governments to hedge themselves against equity shocks. Monetary policy shocks of a hegemon currency issuer affect returns obtained by banks for the risky loans they concede, altering these agents' risk pricing and balance sheet composition. Main results outline that global monetary policy tightening reduces the returns of risky global loans, inducing global banks to reduce risky loan creation, ultimately decreasing both production and consumption volatility internationally. Two more secondary results arise. First, local monetary authorities may counteract global monetary policy spillovers, but this will entail a trade-off between boosting production and reducing consumption volatility. Second, both global and local expansive monetary policy increase the demand for global safe assets, relaxing the budget constraint of monopolistic global safe asset issuers. Understanding the international safety appetite mechanism of transmission appears to be of critical importance as it may impact the effectiveness of monetary policy in open economies as well as its optimal design.